Congenital diaphragmatic hernia in identical twins - Mustafa T Gurbaz; Ahmet Kazez; Unal Bakal; Tugay Tartar; Fikret Ersoz; Yunus Colakoglu (Wolters Kluwer Medknow Publications, 2012)
Congenital diaphragmatic hernia (CDH, Bochdalek type) is rarely seen in both members of identical twins. Herein, we report a 37 weeks' twins with CDH along with a brief review of the literature. Both the neonates survived.